One-step versus two-step screening for diagnosis of gestational diabetes mellitus in Iranian population: A randomized community trial - Ramezani Tehrani, Fahimeh; Rahmati, Maryam; Farzadfar, Farshad; Abedini, Mehrandokht; Farahmand, Maryam; Hosseinpanah, Farhad; Hadaegh, Farzad; Torkestani, Farahnaz; Valizadeh, Majid; Azizi, Fereidoun; Behboudi-Gandevani, Samira (Frontiers in Endocrinology, 2023)
Objectives: There is considerable worldwide controversy regarding optimal screening and diagnostic approaches for GDM. This study aimed to compare the prevalence, maternal and neonatal outcomes of a One-step with a Two-step approach for the screening and diagnosis of GDM in a large community sample of pregnant women. Methods We conducted a secondary analysis of a randomized community non-inferiority trial of GDM screening in Iran. For the current study, all pregnant women who met the inclusion criteria were randomized into two groups for GDM screening. The first group of women (n=14611) was screened by a One-step screening approach (75-g two-hour oral glucose tolerance test (OGTT)) and the second group (n=14160) by a Two-step method (the 50-g glucose challenge test followed by the 100-g OGTT). All study participants were followed until delivery, and the adverse maternal and neonatal outcomes were recorded in detail. Results: GDM was diagnosed in 9.3% of the pregnant women who were assigned to the One-step and in 5.4% of those assigned to the Two-step approach with a significant difference between them (P<0.001). Intention-to-treat analyses showed no significant differences between the One-step and the Two-step group in the unadjusted risks of the adverse pregnancy outcomes of macrosomia, primary cesarean-section, preterm birth, hypoglycemia, hypocalcemia, hyperbilirubinemia, preeclampsia, neonatal intensive care unit admission, birth trauma, low birth weight, and intrauterine fetal death. Results remained unchanged after adjustment for potential confounder variables including gestational age at enrollment and delivery, maternal body mass index, gestational weight gain, type of delivery, treatment modality, and GDM diagnosis in the first trimester. Conclusion: We found that although the rates of GDM more than doubled with the One-step strategy, the One- vs Two-step method was not significantly associated with improved adverse maternal and neonatal outcomes. These findings may warn that more caution should be exercised in adopting the One-step method worldwide. Future research is needed to assess the long-term harm and benefits of those approaches to GDM screening for both mothers and their offspring.